2006
DOI: 10.1097/01.mlg.0000191472.02720.1f
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Evaluating True Vocal Fold Motion Before Thyroid Surgery

Abstract: Patients without voice complaints can have VF motion impairment. Patients can also have VF motion impairment contralateral to the thyroid lesion. Preoperative VF examination helps counsel patients appropriately about the risks of surgery and helps outline a plan for the extent of surgery while minimizing the medicolegal ramifications of iatrogenic RLN injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 14 publications
3
81
1
4
Order By: Relevance
“…100 Of 340 pre-thyroidectomy patients, VF motion abnormalities were found in 6.5%. 101 A finding of VF paralysis on preoperative examination strongly suggests the presence of invasive thyroid malignancy. In 1 study, the rate of preoperative VF paralysis in a series of patients with invasive thyroid malignancy was over 70% versus 0.3% in the control group of patients with noninvasive thyroid disease.…”
Section: Action Statement Profilementioning
confidence: 99%
See 1 more Smart Citation
“…100 Of 340 pre-thyroidectomy patients, VF motion abnormalities were found in 6.5%. 101 A finding of VF paralysis on preoperative examination strongly suggests the presence of invasive thyroid malignancy. In 1 study, the rate of preoperative VF paralysis in a series of patients with invasive thyroid malignancy was over 70% versus 0.3% in the control group of patients with noninvasive thyroid disease.…”
Section: Action Statement Profilementioning
confidence: 99%
“…One-third of 340 such patients evaluated preoperatively had no voice complaints. 101 Two studies reported limited sensitivity of vocal symptoms in the prediction of vocal fold paralysis ranging from 33% to 68%. 101,102 In one study, one third of 98 patients with postoperative vocal fold paralysis were ultimately judged to be asymptomatic in terms of vocal symptoms.…”
Section: Action Statement Profilementioning
confidence: 99%
“…64 Other studies reported one-third of all patients will have some degree of preoperative vocal cord hypomobility on examination. 66,67 In instances of preoperative cord deficit being caused by benign goitre, it is reported that 89% will recover full function after surgery. 68 Pre-intubation laryngoscopy and subsequent assessment has revealed that vocal fold injury can occur in approximately 30% of endotracheal intubations and 4% of post-operative RLNP are attributable to intubation injury.…”
Section: Perioperative Evaluation Of Rln Functionmentioning
confidence: 99%
“…Second, if recurrent laryngeal nerve palsy is identified before surgery, the surgeon can be prepared in case that an accidental injury of the contralateral healthy side occurs, and early detection of need for tracheostomy will prevent the patients from suffocation [2][3][4][5] . At last, since recurrent laryngeal nerve palsy is frequent complication occurring in thyroid surgery, absence of postoperative recurrent laryngeal nerve palsy can be one of the criteria for proper surgical quality [6,7] . Laryngeal fiberscope, now electroendoscope is in popular use in Japan, is the most common and reliable instrument for directly checking vocal fold (VF) mobility, but is a little invasive and uncomfortable for patients [2,8] .…”
Section: Introductionmentioning
confidence: 99%